Sharia Maqashid Review of an Additional Cost of 10% (PB1 tax) to Consumers by Culinary Business Owners : (Study Case of Restaurant&Cafe Medan City and Meulaboh-Aceh Barat) - Andri Soemitra; Susi Herawati; M. Shabri Abd. Majid (Brilliant International Journal Of Management And Tourism, 2025)
This study analyzed the Kuliners business (restaurant and cafe) of West Aceh City of Meulaboh Aceh with a comparison of Medan City Regional Regulations that bestowed an additional 10% (PB1) cost of the total purchases to the Kuliners visitors by the Kuliners business owner imposed by the Medan City Regional Regulation, it should reconstruct the application of the restaurant tax rules by moving the Islamic economy principles. In this study using service costs variables, the basis of tax use and PB consumption tax 1 (10%). The results of this study indicate that, the implementation of an additional 10% cost (PB I) by the culinary business owner of restaurants or cafes has not used ethics and morals in the perspective of sharia maqashid, and is expected to refer to the principles of Islamic economics, so that the realization of sharia maqashid as a foundation in the economy for regional income for the continuation of economic development. This study uses the moderated regression analysis approach and with field information data collection techniques and literature study analysis.